The Holsneset boathouse site: A research excavation report - Wickler, Stephen (Tromura, 2025)
This report provides an overview of results from research excavations by the author in 2024 at the Holsneset medieval boathouse site. The primary objective was to provide a chronological framework for the construction and use of what is arguably the largest archaeological boathouse structure in northern Norway. The Holsneset excavation is also a key case study within an overarching research project that explores the role of monumental boathouses along the main sailing route through northern Norway as an expression of maritime communication and power in the late Iron Age and medieval period.Although the excavations in 2024 were limited to two parallel 4.5 x 0.5 m trenches extending across the boathouse floor, the results provide significant insights into boathouse construction that include floor and inner wall profiles. Surface features reveal two construction phases. In the first phase, radiocarbon dated by two samples with a collective age range of cal AD 1163-1229, the estimated internal length of the structure was c. 20 m with a vertical stone facing up to 1 m high along the interior wall. The parallel wall mounds from the original structure were extended towards the shoreline to construct a modified boathouse with an internal length of 39 m. The second phase boathouse extension utilized bedrock outcrops as a foundation for wall construction coupled with shell sand fill to build up new wall mounds. No reliable radiocarbon age estimates were obtained from this phase. The location, monumental dimensions and construction methods of the Holsneset boathouse strongly suggest that it was built and extended specifically for the leidang maritime defense system.The initial excavation trench was placed towards the front of the original boathouse. The second trench was placed at the transition between the two structures where the entrance to the original boathouse overlaps with the extended boathouse. A stacked stone feature, c. 1 m wide and 15 cm high, was constructed at the center of the floor in the trench at the entrance to the original boathouse. This structure is interpreted as a keel support assisting the movement of large vessels in and out of the boathouse. Stone alignments were placed along both sides of this central structure. Similar alignments are also present in the trench placed further back in the original boathouse along a stone lined keel trench. The alignments in both trenches would have supported the hulls of large vessels on the poorly drained surface where the boathouse was built. Due to poor preservation conditions, the artifact assemblage was limited to highly corroded boat rivet fragments. No bone was preserved, and it was also difficult to collect sufficient charcoal for radiocarbon dating.
Keywords: archaeology; archaeological excavation; lofoten; boathouse; medieval period; pastoralism